Integrated Brand Communication (IBC): Maximizing the Voice, Minimizing the Noise - Bambang Sukma Wijaya (Jobmark: Journal of Branding and Marketing Communication, 2022)
Integrated Brand Communication (IBC) refers to unifying a brand's messaging to make it consistent across all media used to reach its target audience. It is a strategic approach that guides communication and tactics across all branding channels. The main goal of IBC is to maximize the brand's voice and minimize the noise that may distract or confuse the consumers, both internally and externally. IBC can help with brand-building, campaign effectiveness, and customer loyalty in long-lasting brand relationships by aligning the primary brand message and using the right mix of marketing omnichannel. This article provides a roadmap, strategic concepts, and practical guides for optimizing brand message clarity amidst the buzz of branding and mass communication explosions.